The catalytic performance of metal complexes immobilized on SBA-15 in the ring opening polymerization of ε-caprolactone with different metals (Ti, Al, Zn and Mg) and immobilization procedures1. Issue 9 (7th March 2015) - Pérez, Yolanda; del Hierro, Isabel; Zazo, Lydia; Fernández-Galán, Rafael; Fajardo, Mariano
<x xml:space="preserve">Abstract</x> A family of heterogeneous catalysts has been prepared by employing different strategies.